Similar efficacy of broad-range ITS PCR and conventional fungal culture for diagnosing fungal infections in non-immunocompromised patients. Issue 1 (December 2016) - Rampini, Silvana; Zbinden, Andrea; Speck, Roberto; Bloemberg, Guido
Abstract Background Broad-range fungal inter spacer region (ITS) polymerase chain reaction (PCR) has been evaluated for the detection and identification of fungi in clinical specimens from severely immunocompromised patients, but not in non-selected patients. Thus, the aim of this study was to compare the diagnostic performance of ITS PCR with that of fungal culture and to investigate its clinical impact on the diagnosis of fungal infections in non-immunocompromised patients. The corresponding patients' data were retrieved by detailed medical chart reviews. Results Results from 251 specimens showed a high concordance of 89.6 % for ITS PCR and fungal culture. The analytical sensitivity and specificity of ITS PCR considering culture as gold standard were 87.7 and 90.3 %, respectively, the positive and negative predictive value (PPV and NPV) were 76 and 95.5 %, respectively. Assessing the clinical probability of a fungal infection based on detailed chart reviews, PCR had a clinical sensitivity of 88.9 %, a specificity of 86.3 %, a PPV of 64.0 % and a NPV of 96.6 %. The overall performance of fungal broad-range PCR was similar to that of culture. Conclusions Our data show that, in non-selected and non-immunocompromised patients, the performance of ITS PCR is similar to that of culture for detecting fungal infections, not the least because sensitivity of culture in patients under antifungal treatment is surprisingly high. Compared to culture, PCR has the advantage of a rapid time-to-result (approximately two working days), proper identification of rare pathogens, prompt initiation of a species-targeted antifungal treatment, and prospects for automation.